Informatics curriculum implementation in Kurikulum Merdeka: case study SMPN 26 Bandung - Ester Dameria Siboro (Himpunan Pengembang Kurikulum Indonesia, 2026)
This study investigates the implementation of the Informatics curriculum within the Kurikulum Merdeka framework at SMPN 26 Bandung, a public lower secondary school located in an urban area of West Java, Indonesia. Using a qualitative case study approach, this research analyzes the first-year implementation of Informatics as a compulsory subject reintroduced in the 2021/2022 academic year. Data were collected through in-depth semi-structured interviews with Informatics teachers and direct observations of classroom practices and learning facilities. The findings reveal key implementation challenges, including the limited availability of qualified Informatics teachers, insufficient technological infrastructure, and diverse levels of students’ digital readiness. Despite these constraints, the school has managed to implement basic Informatics instruction emphasizing practical computer literacy, particularly proficiency in Microsoft Office applications. This study contributes to the discourse on curriculum implementation in resource-constrained educational contexts. It provides policymakers and school leaders with empirical insights into the realities of curriculum reform at the secondary school level. The study concludes that the successful implementation of specialized subjects such as Informatics requires comprehensive support systems, including continuous teacher professional development, adequate infrastructure, and context-sensitive curriculum adaptation. Abstrak Penelitian ini menginvestigasi implementasi kurikulum Informatika dalam kerangka Kurikulum Merdeka di SMPN 26 Bandung, sebuah sekolah menengah pertama negeri yang berlokasi di wilayah perkotaan Jawa Barat, Indonesia. Penelitian ini menggunakan pendekatan kualitatif dengan desain studi kasus untuk menganalisis pelaksanaan mata pelajaran Informatika pada tahun pertama penerapannya sebagai mata pelajaran wajib pada tahun ajaran 2021/2022. Data dikumpulkan melalui wawancara mendalam semi-terstruktur dengan guru Informatika serta observasi langsung terhadap praktik pembelajaran dan fasilitas pendukung di sekolah. Hasil penelitian mengidentifikasi tantangan implementasi utama, meliputi keterbatasan ketersediaan guru Informatika yang kompeten, infrastruktur teknologi yang belum memadai, serta keberagaman tingkat kesiapan digital murid. Meskipun menghadapi keterbatasan tersebut, sekolah tetap mampu menyelenggarakan pembelajaran Informatika dasar dengan penekanan pada penguasaan keterampilan literasi komputer praktis, khususnya penggunaan aplikasi Microsoft Office. Penelitian ini berkontribusi pada pemahaman dinamika implementasi kurikulum dalam konteks pendidikan dengan keterbatasan sumber daya serta memberikan implikasi empiris bagi perumus kebijakan dan pengelola sekolah terkait pelaksanaan reformasi kurikulum. Studi ini menyimpulkan bahwa keberhasilan implementasi mata pelajaran khusus seperti Informatika memerlukan sistem dukungan yang komprehensif, mencakup pengembangan profesional guru secara berkelanjutan, penyediaan infrastruktur yang memadai, serta adaptasi kurikulum yang sensitif terhadap konteks sekolah. Kata Kunci: kurikulum informatika; Kurikulum Merdeka; literasi digital; pendidikan menengah